2014
DOI: 10.1186/2052-3211-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perception of generic and electronic prescribing: A descriptive study from Jordan

Abstract: ObjectivesThe aim of this study was to investigate Jordanian physicians’ perception and attitudes toward generic medicines and generic substitution. It also aimed to examine factors that affect physicians’ pattern of prescribing, and to evaluate their opinion regarding future introduction of Electronic Prescribing (EP) in Jordan.MethodsA cross-sectional descriptive study involving Jordanian physicians working in both public and private sectors was undertaken, using a self-administrated anonymous questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 42 publications
4
36
2
Order By: Relevance
“…From the current study 72% of physicians claimed that they always prescribe generic medicine, which is slightly lower than the study finding in Ghana which revealed 79.2 % of medicines prescribed by generic name, the reason for the difference of the two finding may be a study conducted in Ghana only consider antibiotic but the current study couldn't specify medicine group, the other study conducted in Jordan depicted that from the physician's 62.8% (often) and 14.6% (very often) prescribe generic medicine instead of an originator brand which is comparable with our findings. 35,36 In the current study, 28% of physician claimed that brand medicines are safer than generic medicine which is comparable with one systematic review that showed a greater proportion of doctors (836/2928, 28.54%, 95%) believed that generic medicines are equally safer with brand medicine. In this review significantly higher proportion of physicians held the view that generic drugs were less effective than their brand name equivalents (1450/5056; 28.68%) but in the current study, 34% of physician's couldn't accept locally produced medicines as equally effective as original brand medicines.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…From the current study 72% of physicians claimed that they always prescribe generic medicine, which is slightly lower than the study finding in Ghana which revealed 79.2 % of medicines prescribed by generic name, the reason for the difference of the two finding may be a study conducted in Ghana only consider antibiotic but the current study couldn't specify medicine group, the other study conducted in Jordan depicted that from the physician's 62.8% (often) and 14.6% (very often) prescribe generic medicine instead of an originator brand which is comparable with our findings. 35,36 In the current study, 28% of physician claimed that brand medicines are safer than generic medicine which is comparable with one systematic review that showed a greater proportion of doctors (836/2928, 28.54%, 95%) believed that generic medicines are equally safer with brand medicine. In this review significantly higher proportion of physicians held the view that generic drugs were less effective than their brand name equivalents (1450/5056; 28.68%) but in the current study, 34% of physician's couldn't accept locally produced medicines as equally effective as original brand medicines.…”
Section: Discussionsupporting
confidence: 82%
“…Another study in Malaysia revealed cost of drugs 31(88.6%) and socio-economics status of the patients 16(45.7%) are factors that influences clinicians prescribing intent; this is lower than that of the current study likewise, the study was done in Jordan showed 58.5% of physician's believed that the cost is important, 10.6% believed that the cost is highly important, whereas 30.9% of the physicians believed that the cost is not important at all but the result of Jordan study also a bit higher than from that of our study. 35,39 The difference in study participants, sample size and medicine specification could be the probable reason for the difference in findings. From the current study above half 27 (58%) of the physicians strongly agreed or agreed that they prescribe brand medicines due to the medical representative influence which is higher than the study conducted previously in similar study area which reports 40 (48.2%) of the physicians believed that their prescribing behaviors were influenced by visits of MRs and reports from Kentucky physicians indicated that they used information supplied by pharmaceutical representatives in their clinical practice 5.4% daily, 31.3% weekly, 47.7% monthly, and 14.4% yearly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this conventional belief is gradually challenged, as latest empirical studies have shown that MRs do not always influence prescribing behaviour [20] and are related to irrational prescribing of medications. [45] Eldahiyat et al [46] reported that drug sales representatives claimed to be of least importance in the drug prescribing decision. Thus, the perception portrayed in literature is not as clear as it may seem at first glance.…”
Section: Physician Prescribing Decision Influences Mohsen Ali Murshidmentioning
confidence: 99%
“…A higher male/female ratio showed that the participation was slightly higher by male physicians compared to females. A study by El-Dahiyat et al also showed similar results with higher number of male physicians [15]. In Alfahad et al study which focused on consumer's perception, more than half of the respondents were male [12].…”
Section: Discussionmentioning
confidence: 73%